Pemanfaatan Media Digital dalam Pendidikan Kewarganegaraan Untuk Penguatan Etika Sosial di Kalangan Remaja - Ragil, Alisa; Kartika, Amelia; Azhara, Nabila Rahma; Aswat, Nur Asia; Sari, Riska Puspita (CV. Kurnia Grup, 2025)
This study aims to examine the role of digital media in civic education to strengthen social ethics among adolescents through a literature review. The method used is a literature study that analyzes national and international scientific articles published in the last five years (2019–2024). The findings indicate that digital media plays a significant role in promoting civic values and social ethics by providing interactive, relevant, and contextual learning experiences for adolescents. However, challenges such as the spread of hoaxes, hate speech, low digital literacy, and negative online behavior remain major obstacles. Therefore, integrated pedagogical strategies are required, including digital literacy, project-based learning, and collaboration among schools, families, and communities. With such approaches, digital media can serve as an effective instrument in shaping young generations to become ethical, critical, and responsible citizens.